ANTESEDEN NIAT PEMBELIAN PADA PRODUK PREMIUM PERHIASAN MUTIARA BERBASIS ONLINE STORE - Intan Hidayah; Aftoni Sutanto; Purwoko Purwoko; Zunan Setiawan; Fitroh Adhilla (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study examines customer value perception models including product quality, service quality, innovation, price and store image. How to understand the relationship between antecedents purchase intention online store by testing the relationship using PLS SEM. This study design collects 207 respondents which can be used through on linesurvey. Partial least squares structural equation modeling method (PLS-SEM) was carried out to validate the proposed hypothesis. The results showed that the perceived values inonline store dangenerally each motivates purchase intention. Furthermore, the findings of this study provide several important theoretical and practical implications for based marketing strategies online store.